Complete traumatic transection of thoracic spinal cord in a pediatric patient - Rachit Garg; Bhakti U Sarangi; Guruprasad Hassan Shankar; Ajay Walimbe (Wolters Kluwer Medknow Publications, 2022)
With pediatric spinal cord injuries themselves being an infrequent event worldwide, complete transection of the spinal cord forms an extremely small subset of the same. Moreover, complete transection of spinal cord without the concurrent presence of vertebral compression fractures has rarely been reported in the pediatric age group. We hereby present a pediatric case with traumatic brain injury as well as complete thoracic spinal cord transection and probe the possible mechanisms that contribute to these injuries in the pediatric age group. We also discuss the challenges faced in the diagnostic evaluation as well as the therapeutic dilemmas in the given scenario due to the multiple ongoing issues.